Hapalosiphonacean cyanobacteria (Nostocales) thrived amid emerging embryophytes in an early Devonian (407-million-year-old) landscape - Christine Strullu-Derrien; Frédéric Fercoq; Marc Gèze; Paul Kenrick; Florent Martos; Marc-André Selosse; Karim Benzerara; Andrew H. Knoll (iScience, 2023)
Summary: Cyanobacteria have a long evolutionary history, well documented in marine rocks. They are also abundant and diverse in terrestrial environments; however, although phylogenies suggest that the group colonized land early in its history, paleontological documentation of this remains limited. The Rhynie chert (407 Ma), our best preserved record of early terrestrial ecosystems, provides an opportunity to illuminate aspects of cyanobacterial diversity and ecology as plants began to radiate across the land surface. We used light microscopy and super-resolution confocal laser scanning microscopy to study a new population of Rhynie cyanobacteria; we also reinvestigated previously described specimens that resemble the new fossils. Our study demonstrates that all are part of a single fossil species belonging to the Hapalosiphonaceae (Nostocales). Along with other Rhynie microfossils, these remains show that the accommodation of morphologically complex cyanobacteria to terrestrial ecosystems transformed by embryophytes was well underway more than 400 million years ago.